2017
DOI: 10.1037/xge0000239
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evaluative pairings and evaluative statements: How effectively do they shift implicit attitudes?

Abstract: Six experiments, involving a total of 6,492 participants, were conducted to investigate the relative effectiveness of repeated evaluative pairings (REP; exposure to category members paired with pleasant or unpleasant images), evaluative statements (ES; verbally signaling upcoming pairings without actual exposure), and their combination (ES + REP) in shifting implicit social and nonsocial attitudes. Learning modality (REP, ES, and ES + REP) was varied between participants and implicit attitudes were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
134
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(153 citation statements)
references
References 105 publications
16
134
3
Order By: Relevance
“…Results. Attitude IAT scores significantly differed from each other across the control and experimental conditions [t(156.01) = 5.70, P < 0.0001, BF 10 = 1.09 × 10 6 , Cohen's d = 0.78 (study 2A) and t(117.46) = 4.47, P < 0.0001, BF 10 = 1.59 × 10 3 , Cohen's d = 0.73 (study 2B)], replicating well-established evaluative conditioning effects involving the same stimulus materials(57). Crucially, parallel changes in belief IAT scores were also observed.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Results. Attitude IAT scores significantly differed from each other across the control and experimental conditions [t(156.01) = 5.70, P < 0.0001, BF 10 = 1.09 × 10 6 , Cohen's d = 0.78 (study 2A) and t(117.46) = 4.47, P < 0.0001, BF 10 = 1.59 × 10 3 , Cohen's d = 0.73 (study 2B)], replicating well-established evaluative conditioning effects involving the same stimulus materials(57). Crucially, parallel changes in belief IAT scores were also observed.…”
supporting
confidence: 65%
“…In fact, we believe that the relationship between implicit social cognition and language is bidirectional. However, we highlight this particular direction here because, unlike the opposite direction, it (i) offers a clear point of causal intervention in the system and (ii) has been demonstrated empirically (57). ]…”
Section: Discussionmentioning
confidence: 99%
“…As such, if the present revaluation paradigm successfully shifts explicit evaluations of a stimulus, such learning should also be reflected by implicit measures of evaluation. Second, in studies involving novel targets, such as the present one, patterns of convergence between explicit and implicit evaluations are common because participants do not have access to any information about the targets other than the information provided by the experimenter (12). Moreover, in this setting, pressures to act in a socially desirable manner, known to result in dissociations between explicit and implicit evaluations (20), are unlikely to operate.…”
Section: The Present Projectmentioning
confidence: 86%
“…repeatedly demonstrated that implicit evaluations can be flexibly updated via purely verbal instructions and that such updating need not involve direct experience with any stimulus (12). The preponderance of such findings has prompted some to abandon a dual-process perspective on evaluative learning altogether and to replace it with a model of evaluative learning that relies on a single propositional process (13)(14)(15).…”
mentioning
confidence: 99%
“…As a matter of fact, recent research shows that constructs measured by the IAT can be formed through fully deliberate learning processes (e.g. Gast & De Houwer, 2012;Kurdi & Banaji, 2017;Van Dessel, De Houwer, Gast, & Smith, 2015) and that people are able to consciously introspect their IAT score (Hahn, Judd, Hirsch, & Blair, 2014). More generally, that indirect measures reflect the operation of either independent learning pathways or behavioral expression pathways has been questioned lately (for a recent discussion, see Corneille & Stahl, 2018) Instead, the current findings may suggest that students' intentions are less stable than their identification to the field.…”
Section: Discussionmentioning
confidence: 99%